2014
DOI: 10.2174/1381612820666140130201131
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of the Neuroimmunoendocrine System and Aging

Abstract: The health maintenance depends on the preservation of the homeostatic systems, such as nervous, endocrine and immune system, and a proper communication between them. In this regard, the circadian system, which promotes a better physiological system functions and thus well being, could be considered part of that homeostatic complex, since the neuroimmunoendocrine system possesses circadian patterns in most variables, as well as circannual or seasonal variations. With aging, an impairment of the homeostatic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…As previous studies have demonstrated, Mel acts as a stimulant under immunosuppressive conditions or as an anti-inflammatory compound during immune responses, including acute inflammation (38)(39)(40)(41). Advantageously, Mel is ubiquitously distributed in all the cellular compartments, and is capable of quickly passing through all the biological membranes (42).…”
Section: A B C Discussionmentioning
confidence: 99%
“…As previous studies have demonstrated, Mel acts as a stimulant under immunosuppressive conditions or as an anti-inflammatory compound during immune responses, including acute inflammation (38)(39)(40)(41). Advantageously, Mel is ubiquitously distributed in all the cellular compartments, and is capable of quickly passing through all the biological membranes (42).…”
Section: A B C Discussionmentioning
confidence: 99%
“…In the opinion of Mate and co-workers [3], impairment of circadian and seasonal fluctuations of immune functions in human aging may be connected with disturbances of melatonin production. According to our data, the thymic endocrine function in thymulin production is the important part of chronobiological organization of immune system [19,27].…”
Section: Thymulinmentioning
confidence: 98%
“…In aging there occurs dyscoordination of rhythms and disturbance of adaptive capacity of many organism functions, in particular of the neuroendocrine and immune systems [2,3]. Of a special interest is the regulator of biorhythms of the pineal gland hormone, melatonin, and the regulator of immune function of the thymic hormone, thymulin [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The studies in this area indicate that time change can cause the disturbance of the balance between genes, proteins, the activity of endocrine glands and eventually brain's cognitive activities such as memory and learning (Mate et al, 2014; W. E. Bunney & B. G. Bunneym, 2000;Wyatt et al, 1999). For different reasons such as economical motives and others, changes in working hours are carried out by many countries (Rutenfranz et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, these changes will lead to changes in circadian rhythm activities of neuron systems and glands and this in return will cause stress in people (Lucas et al, 2012). This stress is considered as a chronic stress in people who have to travel long distances with ultra sound airplanes or the people who have to do shift work and it may led to different changes in the brain activity (Mate et al, 2014). Various studies have shown that chronic stress stimulates the hypothalamus-pituitary-adrenal axis (HPA) and increase the cortisol concentration in the blood continuously and chronically (Asalgoo et al, 2015;Bahari et al, 2015;McEwen et al, 1999;Salehi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%